Estoque de carbono em áreas sob diferentes usos na região sul do Amazonas, Brasil - Pinheiro, Elyenayra Nogueira (Brasil, 2019)
Among greenhouse gases, CO2 is the major contributor to increased concentration, due to the large amount emitted to the atmosphere, and some agricultural practices, especially changes in land use and management, that are closely related to this issue. Thus the soil properties and the vegetation present in the site interfere in this emission, since the contents of carbon and carbon stock in the soil has been significantly affected by the land use and management systems. This work aims to evaluate the carbon and carbon stock in areas under different uses in the São Francisco settlement in the Canutama region, Amazonas. Soils were sampled at the crossing points of the meshes, making a total of 80 sample points in each area, and totaling 240 samples per area. Samples with preserved structure and volumetric rings were collected 4.0 cm high and 5.1 cm in diameter, centered between 0.0-0.05, 0.05-0.10 and 0.10-0 depths, 20 m. Then, the levels of organic carbon, soil density and carbon stocks were determined. Data were obtained by descriptive statistical analyzes and the mean, median, standard deviation, variance, coefficient of variation, asymmetry coefficient, kurtosis coefficient, minimum and maximum values were calculated. In addition, the environments were compared using the Tukey test to compare means at 5% probability. All areas presented lower values of organic carbon and carbon stock compared to forest, with the exception of the cupuaçu area. This presented higher values of carbon and organic carbon stocks, demonstrating that the conversion of the forest to the cupuaçu crop did not negatively interfere with the organic matter of the soil.